Religiöser Wandel in muslimischen Gesellschaften Individualisierung, Geschlecht und soziale Milieus - Föllmer, Katja (Universitätsverlag Göttingen, 2022)
Processes of individualization in Egypt, Iran, Lebanon, Senegal and Tunisia are central to current social dynamics and form the key theme of the present volume. The central question is how social transformations inform the field of the religious and how processes of religious change likewise have an impact on social change. The contributions in this volume focus in particular on the realities of life for women from urban middle-class milieus. They show how women's efforts to shape one's individual life may run counter to established social and religious norms. While analyzing milieu-specific dynamics, particular attention is devoted to the question how processes of social and religious change become manifest in both gender and generational relations. Western ideals of modernity, globalized discourses and respective leisure/fashion-practices as well as expressions of individualized lifestyles have an impact on dynamics of social and religious change and are discussed in this volume in specific religious as well as non-religious social contexts.